About some integral inequalities using Riemann-Liouville integrals - Dahmani, Zoubir (General Mathematics, 2012)
In this paper, the Riemann-Liouville fractional integral is used to establish some integral inequalities.
Keywords: ntegral inequalities, Riemann-Liouville fractional integral.